(untitled) (Research, Society and Development, 2020)
Population growth and the consequent demand for food puts strong pressure on the environment, especially in agricultural areas. Brazil, the second largest exporter of food in the world, stands out the important sugarcane, corn and soybean agribusiness commodities. However, for this production to be maintained, agricultural practices such as weed management, pesticide management, and environmental protection practices of natural resources are essential. The method of chemical control of weeds with herbicides has been the most used, placing Brazil as the largest consumer in the world, in quantity. The presence of these molecules in the environment can affect several ecosystems including water resources. The objective of this review was to discuss the potential of contamination of water bodies with herbicides used in the cultivation of soybeans, corn and sugarcane in Brazil. The most traded active ingredients in recent years are glyphosate, 2,4-D, atrazine and diuron. Studies of the monitoring of pesticide residues have indicated that these agrochemicals are present in food, atmosphere, surface water and groundwater. Part of the formulations of the herbicides marketed for the evaluated crops has an environmental classification between Class II (Very Dangerous) and III (Dangerous). Case reports involving herbicide contamination have been described in Brazil and worldwide. Atrazine is the herbicide with the highest number of reports as a water contaminant. Control should be adopted within integrated management to minimize damage, as well as farmers’ awareness of the conscious and sustainable use and monitoring of the bodies responsible for monitoring water resources.